Program Penguatan Moderasi Beragama Menuju Indonesia yang Rukun, Damai dan Toleran di Lingkungan Kementerian Agama Kota Mojokerto - Hasan, Ismail (JURNAL ILMIAH GEMA PERENCANA, 2022)
Islam is a religion that came as rahmatallil alamin or as a mercy for all nature. His arrival is expected to bring love, happiness and perfect peace both in this world and in the hereafter. Along with the development Islam, the world also continues to experience developments in various aspects. There are three challenges in the MB strengthening process. First, development of excessive, overreaching, and extreme religious understanding and practice, the second challenge, emergence truth claims on religious interpretations. The third challenge is an understanding that actually undermines or threatens, even destroys national bonds. "To overcome this problem, Kemenag developed the concept of Religious Moderation. Religious Moderation is a perspective leads people to a middle way. This study uses descriptive qualitative research methods with data analysis techniques in this study is descriptive analysis. The results of the study This program divided into two parts, namely the first with regard to the implementation of the program strengthen religious moderation in Mojokerto City, starting with anxiety seeing the widespread misunderstanding between religious communities due issues and slander that often cannot be accounted for. Various efforts have been made to avoid conflicts and also to maintain peace,program efforts strengthen religious moderation through socialization are carried with various hopes create harmony and a tolerant society. Secondly related to the perception organizers the program to strengthen religious moderation as known that moderation Religion in the Ministry of Religion is a priority, because the current sketch of Indonesia depicts the existence of extremism, claims and intolerance.